Type of Industry and Environmental Disclosure Quality: Evidence from Developing Country - Hidayah, Retnoningrum; Akmal, M; Suryandari, Dhini; Wahyuningrum, Indah Fajarini Sri; Suryarini, Trisni; Kayati, I N; Agustina, Linda; Rohmah, Fian Tri; Zahid, Anwar; Jayanto, Prabowo Yudo (Universitas Negeri Semarang, 2023)
The activities of company give a distinct pollution on the natural environment and communities. This paper aims to examine how the role of type of industry influences the quality of environmental disclosures with multi-theories. The research population is non-financial companies listed on the Indonesia Stock Exchange (IDX). The results point out that profitability could not effects on the environmental disclosure quality. Moreover, type of industry has no effect on environmental disclosure quality. In addition, the type of industry cannot moderate the relationship between profitability and the quality of environmental disclosures. This research proves the type of industry is unable to guarantee the level of quality of environmental disclosure by companies. The level of environmental disclosure quality tends to depend on management awareness in each management. This study give contribution for literature review that legitimacy theory could not be implemented. The large companies do not always prioritize environmental disclosure quality.